UNDERSTANDING THE EDUCATIONAL NEEDS OF JOINT HONOURS DEGREE STUDENTS IN A POST BREXIT UNITED KINGDOM HIGHER EDUCATION SECTOR - Pigden, Louise; Jegede, Francis (PEOPLE: International Journal of Social Sciences, 2018)
The motivation for this research was to explore the lived experience of joint honours students, for whom there is little in the literature at present. The objective was to critique primary data collected from the students via a self-administered questionnaire. This phenomenological methodology permitted and unfiltered view of the students’ learning experiences to be explored. The research is based on a cross-university student survey, conducted over a period of six months. The online survey, which ran between June 2016 and January 2017, involved self-administered questionnaires designed to collect information on the learning experience of students on joint honours degrees, from four different Universities in England. A key finding of this paper is the need for university administrators to pay particular attention to joint honours degrees in their portfolios in the light of the growing and significant number of students opting to study these degrees and the general tendency amongst universities to focus attention on single honours degrees. Particular areas of concern are highlighted where students on joint honours degrees feel improvements in their educational experience could be made. The future scope of the survey results are discussed in the context of Britain exiting the European Union and in relation to the growing debate on the intrinsic value of university education and the increasing necessity for university management to recognise the unique nature of joint honours degrees and design policy to meet the needs of students enrolled on joint honours degrees.